Pengaruh Spiritualitas Tempat Kerja Terhadap Kesejahteraan Mental Karyawan Melalui Kebahagiaan Dan Mindfulness Pada Karyawan - Tanoto, Sherly Rosalina; Sari, Dea Manda (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2024)
Background – The mental well-being of employees is crucial for both the individuals and the organizations they belong to. Employees who enjoy mental prosperity are often more productive, underscoring the importance of fostering a supportive work environment. Aim – This study investigates the impact of workplace spirituality on the mental well-being of employees in Java, examining the roles of happiness at work and mindfulness as intermediary factors. Design/ methodology/ approach – Employing a quantitative approach, this research engaged 352 respondents from various organizations across Java. Data collected were analyzed using SmartPLS 4.0 software, focusing on the relationships between workplace spirituality, happiness at work, mindfulness, and employee mental well-being. Findings – The study reveals that workplace spirituality significantly contributes to both happiness at work and mindfulness. Moreover, it directly influences employee mental well-being. However, while mindfulness serves as an effective mediator in this relationship, happiness at work does not significantly mediate the impact of workplace spirituality on mental well-being. This suggests that the pathway through which workplace spirituality affects employee mental well-being is primarily through mindfulness. Conclusion – Workplace spirituality emerges as a positive force, enhancing employee happiness and mindfulness, which in turn, contributes to better mental well-being. The study underscores the importance of mindfulness as a mediating factor, highlighting its role in leveraging spiritual values in the workplace to support employee mental health. Research Implication – The findings suggest that organizations should consider integrating mindfulness training and spiritual values into their employee development programs. Such initiatives can help mitigate stress, anxiety, and work-related pressures, fostering a healthier and more supportive work environment conducive to employee growth. Limitations – While this study identified happiness at work and mindfulness as potential mediators, the former did not significantly mediate the relationship between workplace spirituality and mental well-being. Future research might explore alternative mediating variables to fully understand the dynamics at play.